Hey there, Maria! De speelruimte van het Ave Maria in hedendaagse uitvaarten - Janieke Bruin-Mollenhorst (Religie & Samenleving, 2024)
Contemporary funeral rituals in the Netherlands are often characterised as secularised and individualised. Therefore, it is intriguing that ‘Ave Maria’ is still among the Top 10 most popular songs that are played during funerals. This article shows various motivations for listening to an Ave Maria: expressing a shared Christian identity; expressing the Christian identity of the deceased; ‘it is a beautiful piece of music’; and ‘it belongs to the funeral’. It is argued that the Ave Maria provides some latitude (speelruimte) in contemporary secularised and individualized funerary culture.